2022
DOI: 10.3390/genes13081362
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Gene Mutation Profiling by Targeted Next-Generation Sequencing in Premenopausal Breast Cancer

Abstract: Breast cancer has distinct etiology, prognoses, and clinical outcomes at premenopausal ages. Determination of the frequency of germline and somatic mutations will refine our understanding of the genetic contribution to premenopausal breast cancer susceptibility. We applied a comprehensive next generation sequencing-based approach to analyze blood and/or tissue samples of 54 premenopausal breast cancer patients treated in our clinic. Genetic testing results were descriptively analyzed in correlation with clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 55 publications
1
1
1
Order By: Relevance
“…The remaining cases exhibited vari"ble 'utations in different combinations (NF1, PTEN, ATR, CHEK2, PMS2, and ATM), as previously reported, showing lower frequencies compared to a set of TP53 and PIK3CA mutations [39]. However, conversely, high-frequency variants were detected in the BLM gene, which was reported to rarely occur in Bca [34,40]. This observation emphasizes the complexity of oncogenic interactions among genes carrying mutations, highlighting that these interactions are not straightforward or linear processes.…”
Section: Discussionsupporting
confidence: 72%
“…The remaining cases exhibited vari"ble 'utations in different combinations (NF1, PTEN, ATR, CHEK2, PMS2, and ATM), as previously reported, showing lower frequencies compared to a set of TP53 and PIK3CA mutations [39]. However, conversely, high-frequency variants were detected in the BLM gene, which was reported to rarely occur in Bca [34,40]. This observation emphasizes the complexity of oncogenic interactions among genes carrying mutations, highlighting that these interactions are not straightforward or linear processes.…”
Section: Discussionsupporting
confidence: 72%
“…Compared with previous studies, [23][24][25] our findings indicate a substantial enhancement in the prognostic capability of specific gene mutations. Notably, the HRs for RFS and OS associated with these mutations were significantly higher than those previously reported.…”
Section: Any Mutation Months Mediancontrasting
confidence: 72%
“… 9 Additionally, more cancer predisposition genes such as TP53, ATM, PALB2, CHEK2 , RAD51C, and RAD51D mutations have been discovered, and better understanding of these genes have led to more genes being integrated into routine multi-gene panel testing (MGPT). 10 , 11 Wider use of MGPT has shown that PGV are quite common and may be present in patients without family history of cancer. 12 , 13 …”
Section: Introductionmentioning
confidence: 99%